The institutional framework for doing sports business: Principles of EU competition policy in sports markets - Oliver Budzinski (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2011)
The competition rules and policy framework of the European Union represents an important institutional restriction for doing sports business. Driven by the courts, the 2007 overhaul of the approach and methodology has increased the scope of competition policy towards sports associations and clubs. Nowadays, virtually all activities of sports associations that govern and organize a sports discipline with business elements are subject to antitrust rules. This includes genuine sporting rules that are essential for a league, championship or tournament to come into existence. Of course, real business or commercial activities like ticket selling, marketing of broadcasting rights, etc. also have to comply with competition rules.
Keywords: 330; Professioneller Sport; Sportmarketing; Sportökonomik; Institutionalismus; Wettbewerbspolitik; Kartellrecht; EU-Staaten